Mejoras a los algoritmos de bioinformática Needleman-Wunsch y K-Band mediante la mejora de la matriz de similitud - Saborio-Arce, Alonso (Instituto Tecnológico de Costa Rica, 2015)
Bioinformatics algorithms are limited by memory and disc management processes due to their large amount of data manipulation, like sequence alignment methods. For example, NeedlemanWunsch algorithm aligns two sequences optimally; it creates a matrix of N rows and M columns, where N and M are the amount of characters each sequence had. Based on the final size of the matrix these problems become restrictive. This thesis’s objective is to set and prove a Needleman-Wunsch algorithm improvement in order to enhance its efficiency. With the fusion of two dynamic programming algorithms and the minimization on the similarity matrix usage the amount of disc and / or memory used by the algorithm will be reduced. The implemented solution is a modification of the K-Band algorithm, which gets the optimal solution parsing the matrix once, differing from its original version that parses it many times. The main feature of the new algorithm is how the band is expanded when the alignment cannot be optimal, that will happen when the parsing is in the border of the band. Some experiments were developed and ran in order to validate the solution created. With the results obtained, it was proved that the proposed improvement of the Needleman-Wunsch algorithm uses the similarity matrix less and improves the memory and disc performance on big sequences
Proyecto de Graduación (Maestría en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2015.
Keywords: Secuencia; Algoritmo; Disco; Desempeño; Memoria